ENHANCEMENT OF THE STRATEGY FOR THE EMPLOYMENT AND INTEGRATION INTO THE WORK ENVIRONMENT OF PERSONS WITH DISABILITIES - Živitere, Marga; Oborenko, Zaiga; Konstantinova, Elina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper is prepared as a forecast of the employment strategy towards to the EU Lisbon goals - to promote employment and social inclusion for all people. The problems are the inadequate employment of persons with disabilities. The objectives of the research study were as follows: to clarify the problem of above mentioned attitude of employers and the main reasons for not hiring people with disabilities several problems can be identified. Information for the paper is gathered through contacting experts - respondents and conducting extensive literature reviews. The research approach was based on the premise that employers with professional training of employees with disability are responsible for recruitment, pre-employment screening and other workplace practices that positively affect the hiring and retention of this group. It is hoped that the outcome of the research study will assist in reducing all forms of existing barriers with special emphasis on attitudinal barriers against prospective employees with disabilities. Furthering the integration of persons with disabilities into the mainstream activities will promote the employment of people with disabilities and thereby would make a considerable effort to integrate inactive labour resources into the labour market to promote the achievement of the EU Lisbon goals.